Corneal Microaneurysm-A Vascular Feature of Conjunctival Squamous Intraepithelial Neoplasia - Stöckl, Victoria; Franchi, Alexander; Palme, Christoph; Steger, Bernhard (Cornea, 2024)
The diagnosis of conjunctival squamous intraepithelial neoplasia (CSIN) can be difficult because of the heterogeneous appearance. Despite established risk factors and diagnostic support by high-resolution optical coherence tomography (hrOCT) and indocyanine green angiography (ICGA), the only reliable diagnostic method is a histological work-up. This case report is the first to describe corneal microaneurysms in CSIN as a vascular feature for conjunctival tumor angiogenesis. An 84-year-old male patient was referred with a suspected diagnosis of pterygium. Biomicroscopic examination revealed a whitish epithelial lesion of conjunctival origin with centripetal corneal growth and extension over 5 limbal hours. Intralesional vascularization showed highly altered morphology with aneurysmal changes. After imaging with hrOCT and ICGA, excision was performed in a "no-touch double-freeze and thaw" technique, followed by histological and immunohistochemical work-up. hrOCT showed an epithelial, hyperreflective lesion with a maximum thickness of 272 µm and sharp central border. ICGA confirmed active perfusion and partial thrombosis of the aneurysmal terminal vascular buds dilated to 405 μm with early dye leakage within the first minute. Histological examination confirmed the clinical diagnosis of CSIN with focal high-grade dysplasia. Postoperatively, there was no recurrence during the observation period of 5 months. Intralesional terminal microaneurysms are a feature of tumor angiogenesis in CSIN. The relevance and frequency of this potential new risk factor for malignancy should be investigated in further studies.